Gamification of vocational distance courses for students of specialties 181 ‘Food technologies’ and 241 ‘Hotel and restaurant business’ - Zaparenko, G.; Lypovy, D. (Problems of Engineer-Pedagogical Education, 2023)
The necessity and expediency of using game elements in e-learning is substantiated. The difference between the concepts of gamification and game-based learning is defined. The article presents an analysis of the experience of using game elements (gamification), as well as game-based learning in various educational establishments around the world. The main advantages and disadvantages of the use of game elements and game-based learning in educational establishments are analyzed. The main advantages for students include increase in the level of motivation to study, improvement in the level of students’ involvement in the studying process and their academic performance, decrease in the level of fatigue, enhancement of the interaction between course participants, and development of soft skills. The main disadvantages include high cost of creating game content, significant time spent on transforming educational information into game content, necessity to engage IT specialists, and difficulty evaluating game results. The most popular platforms for creating game content among teachers are considered. The results of the analysis of the application of game elements created on the Quizlet, Wordwall, and Baamboozle platforms during the study of distance courses "International ethnic cuisines", "Restaurant production technology", "Introduction into the specialty" by the students of the bachelor's and junior bachelor's degrees majoring in Food Technologies and Hotel and Restaurant Business at Ukrainian Engineering Pedagogics Academy during 2019-2022 academic years are presented. The article sheds light on the beneficial effect of the use of the specified game elements on student motivation and engagement, information retention, in particular retention of new terms and classifications, and on the increase in the level of academic performance.